Chlorite Dismutase from perchlorate reducing bacteria. A potential biocatalyst to eliminate chlorinated species from polluted water resources and industrial wastes - Freire, Diana Mendes (2016)
Magnetospirillum (M.) sp. strain Lusitani, a perchlorate reducing bacteria (PRB), was previously isolated from a wastewater treatment plant and phylogenetic analysis was performed to classify the isolate. The DNA sequence of the genes responsible for perchlorate reduction and chlorite dismutation was determined and a model was designed based on the physiological roles of the proteins involved in the pcr-cld regulon. Chlorite dismutase (Cld) was purified from Magnetospirillum sp. strain Lusitani cells grown in anaerobiosis in the presence of perchlorate. The protein was purified up to electrophoretic grade using HPLC techniques as a 140 kDa homopentamer comprising five ~28 kDa monomers. Steady-state kinetic studies showed that the enzyme follows a Michaelis-Menten model with optimal pH and temperature of 6.0 and 5°C, respectively. The average values for the kinetic constants KM and Vmax were respectively 0.56 mM and 10.2 U, which correspond to a specific activity of 35470 U/mg and a turnover number of 16552 s-1. Cld from M. sp. strain Lusitani is inhibited by the product chloride, but not by dioxygen. Inhibition constants KiC= 460 mM and KiU= 480 mM indicated that sodium chloride is a weak mixed inhibitor of Cld, with a slightly stronger competitive character. The X-ray crystallography structure of M. sp. strain Lusitani Cld was solved at 3.0 Å resolution. In agreement with cofactor content biochemical analysis, the X-ray data showed that each Cld monomer harbors one heme b coordinated by a histidine residue (His188), hydrogen-bonded to a conserved glutamic acid residue (Glu238). The conserved neighboring arginine residue (Arg201) important for substrate positioning, was found in two different conformations in different monomers depending on the presence of the exogenous ligand thiocyanate. UV-Visible and CW-EPR spectroscopies were used to study the effect of redox agents, pH and exogenous ligands on the heme environment.